Study of Antibodies to Influenza Neuraminidase N2 - Yulia Desheva; Nadezhda Petkova; Tatiana Smolonogina; Svetlana Donina; Alexey Go (MDPI AG, 2022)
Humoral immunity to influenza neuraminidase (NA) was evaluated among different groups of people including patients with acute influenza infection and healthy people in different age groups using an enzyme linked lectin assay (ELLA). The amino acid composition of NA of seasonal influenza viruses A/Victoria/361/2011(H3N2) and A/Hong Kong/4801/2014(H3N2) differed by 2%, while cross-reacting neuraminidase-inhibiting (NI) antibodies to them in the same serum samples were detected in 10% of cases. Middle-aged patients born from 1977 to 2000 had a high level of hemagglutination-inhibiting (HI) antibodies to A/Hong Kong/4801/2014(H3N2), but almost no NI antibodies, which may indicate that in the case of a change in the hemagglutinin (HA) subtype, this age group will be susceptible to influenza A/H3N2 viruses. Therefore, it could mean there is a need for priority vaccination of this age group with a vaccine against the appropriate strain. It was shown that after intranasal administration of live influenza vaccine (LAIV) for the 2017-2018 season, serum antibody response was not lower compared to that during natural infection. In older people, antibodies to archival A/H2N2 viruses were detected more often than to modern A/H3N2. Since the conversion of antibodies to HA and NA often did not coincide, antibodies to NA can serve as an additional criterion for assessing the immunogenicity of influenza vaccines.